Prototype Of An RFID-Based Door Lock System Using An ESP32 Microcontroller With Telegram Notifications - Dimas Alvian Reza; Belinda Ayuningtyas (International Journal of Health Engineering and Technology, 2026)
Door security is an important aspect of restricting access and protecting assets from unauthorized use. This study aims to design and develop a door lock prototype based on the ESP32 microcontroller by integrating an RFID RC522 module, a 4×4 matrix keypad, a 16×2 I2C LCD, an SG90 servo motor, LEDs, a buzzer, and a Telegram Bot for monitoring and remote control. The system implements RFID card and keypad password authentication, equipped with an automatic blocking feature after three consecutive incorrect password attempts and real-time notifications via Telegram. Testing results showed that the ESP32 Expansion Board received an input voltage of 12.28 VDC and successfully distributed operating voltages to all components, including 3.2 VDC for the RFID RC522, 5 VDC for the 16×2 I2C LCD and SG90 servo motor, and approximately 3 VDC for the LEDs. The RFID module was able to read cards at a maximum distance of 4 cm, while the servo motor successfully opened the door for 5 seconds through RFID and keypad authentication, and 3 seconds through Telegram commands. All components operated according to the design, demonstrating that the system can enhance door access security, support real-time activity monitoring, and provide a practical and reliable Internet of Things (IoT)-based door security solution.